2016
DOI: 10.1016/j.amjmed.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Resident Case Review at the Departmental Level: A Win-Win Scenario

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among the 46 studies, 35 represented unique institutions and 11 were same authors/institutions describing different aspects of the process or domains. The types of articles identified included 14 descriptive [ 11 – 24 ], three editorials [ 25 – 27 ] 15 prospective [ 28 42 ], seven quality improvement projects [ 12 , 43 48 ], and ten retrospective [ 11 , 30 , 49 – 56 ]. The 16 domains of successful care review that were identified for abstraction are presented and defined in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 46 studies, 35 represented unique institutions and 11 were same authors/institutions describing different aspects of the process or domains. The types of articles identified included 14 descriptive [ 11 – 24 ], three editorials [ 25 – 27 ] 15 prospective [ 28 42 ], seven quality improvement projects [ 12 , 43 48 ], and ten retrospective [ 11 , 30 , 49 – 56 ]. The 16 domains of successful care review that were identified for abstraction are presented and defined in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…One of the strengths of our program is the interprofessional group of faculty and PS experts involved in the development and delivery of the curriculum. Although other curricula have been primarily delivered by using online modules ( 14 , 20 ), by chief residents ( 13 , 18 , 20 , 26 ), by resident QI–PS councils ( 15 , 27 ), by faculty with QI–PS interests ( 13 , 18 , 22 , 28 ), or by including residents in institutional QI–PS frameworks ( 23 , 29 ), a novel feature of our curriculum is the direct integration of a local PS expert from our institution’s office of PS into the classroom. The PS analyst was intimately involved with the design of the curriculum and served as the moderator for the active-learning sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of this institutional curriculum include the small sample size, as well as the timing and continuity, which are common barriers in GME curricula ( 19 , 29 ). Resident attendance was variable because of time off, vacation, and night-shift responsibilities, which also affected curricular evaluations because only those present for the respective session took part in the assessment.…”
Section: Discussionmentioning
confidence: 99%
“… 14 16 Yet other programs conduct patient safety education by fostering resident involvement in morbidity, mortality, and improvement case conferences 17 19 or departmental peer review committees. 20 , 21 These educational methods are certainly valuable components of patient safety education; however, they are not sufficient in addressing the deficiencies outlined in the 2021 CLER report given that they typically do not emphasize the importance of reviewing low-harm or near-miss events and do not necessarily engage all residents in event review processes. 2 They additionally are not sufficient in fulfilling the goals of the PEI PSC given that they do not describe active participation in event review for PGY 1 learners.…”
Section: Introductionmentioning
confidence: 99%